2018
DOI: 10.1126/sciadv.aao1705
|View full text |Cite
|
Sign up to set email alerts
|

Stable organic thin-film transistors

Abstract: Organic thin-film transistors exhibit an unprecedented level of reliability, bringing them closer to commercialization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(95 citation statements)
references
References 35 publications
3
92
0
Order By: Relevance
“…The use of a gate dielectric consisting of multilayers instead of a single layer can also suppress bias stress–induced charge trapping. Jia et al reported that in the bilayer gate dielectric approach the addition of a second dielectric layer onto the first dielectric layer in OFETs can effectively compensate for charge trapping at the first dielectric layer . They investigated the bias stress stability of small‐molecule 2,8‐difluoro‐5,11‐bis(triethylsilylethynyl) anthradithiophene FETs with a bilayer dielectric consisting of the fluoropolymer Cytop and metal oxide Al 2 O 3 :HfO 2 .…”
Section: Recent Progress In Improving the Bias Stress Stability Of Ormentioning
confidence: 99%
“…The use of a gate dielectric consisting of multilayers instead of a single layer can also suppress bias stress–induced charge trapping. Jia et al reported that in the bilayer gate dielectric approach the addition of a second dielectric layer onto the first dielectric layer in OFETs can effectively compensate for charge trapping at the first dielectric layer . They investigated the bias stress stability of small‐molecule 2,8‐difluoro‐5,11‐bis(triethylsilylethynyl) anthradithiophene FETs with a bilayer dielectric consisting of the fluoropolymer Cytop and metal oxide Al 2 O 3 :HfO 2 .…”
Section: Recent Progress In Improving the Bias Stress Stability Of Ormentioning
confidence: 99%
“…However, these organic‐based RRAMs are difficult to be apply for skin‐attachable wearable devices due to their sensitivity to external environmental factors. Specifically, moisture, which is both a component of bodily fluids and exists environmentally, can cause degradation of organic materials and fatally affect the memory operation of organic‐based RRAMs. Therefore, resolving issues such as degradation of the electrical performance of organic‐based RRAMs due to external moisture is important prior to implementation in skin‐attachable wearable devices.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly stable devices can be achieved using molecular additives [17] and bi-layer gate-dielectrics, [18] reaching parity with microcrystalline silicon and amorphous oxide devices. Stability investigations on organic field-effect transistors (OFETs) with lateral channels show threshold voltage shifts ranging from several volts after an hour of bias-stress down to less than 100 mV.…”
Section: Introductionmentioning
confidence: 99%